2014
DOI: 10.1016/j.ultrasmedbio.2013.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Application of Acoustic Bessel Beams for Handling of Hollow Porous Spheres

Abstract: ABSTRACT-Acoustic manipulation of porous spherical shells, widely used as drug delivery carriers and magnetic resonance imaging contrast agents, is investigated analytically. The technique used for this purpose is based on the application of high-order Bessel beams for as a single-beam acoustic manipulation device, using which particles lying on the axis of the beam can be pulled toward the beam source. The exerted acoustic radiation force is calculated using the standard partial-wave series method and the wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…In the case of a zero-order Bessel beam (ZOBB), for instance, numerical studies have shown that the radiation force on rigid/soft particles is always repulsive, whereas that for acoustically penetrable objects may become negative under specific conditions. [1][2][3][4][5][6][7][8][9][10][11][12] In the absence of gradient and absorption forces, this can only be interpreted to be due to the scattering forces and the structural properties of the object itself. Despite the recent works on the emergence of NRFs due to Bessel beams, [3][4][5][6][7] to the best knowledge of the author, the relation between the structural properties of the particles, e.g., mechanical properties and eigenfrequencies, and the emergence of NRFs on spheres due to an acoustic ZOBB has not been studied before.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the case of a zero-order Bessel beam (ZOBB), for instance, numerical studies have shown that the radiation force on rigid/soft particles is always repulsive, whereas that for acoustically penetrable objects may become negative under specific conditions. [1][2][3][4][5][6][7][8][9][10][11][12] In the absence of gradient and absorption forces, this can only be interpreted to be due to the scattering forces and the structural properties of the object itself. Despite the recent works on the emergence of NRFs due to Bessel beams, [3][4][5][6][7] to the best knowledge of the author, the relation between the structural properties of the particles, e.g., mechanical properties and eigenfrequencies, and the emergence of NRFs on spheres due to an acoustic ZOBB has not been studied before.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Studies have shown that spherical particles placed on the axis of a Bessel beam may be attracted toward the source of the beam for appropriately selected beam parameters (shape and frequency) and particle properties (optical or mechanical). [1][2][3][4][5][6][7][8][9][10][11][12][13] Several theoretical studies have been carried out over the past few years to explore the feasibility of using ordinary (zeroth-order) and high-order Bessel beams for handling of on-axis objects with different mechanical properties. [3][4][5][6][7][8][9][10][11][12] The scattering of Bessel beams by liquid, solid elastics, and porous spheres have also been investigated in some recent papers.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations